The Prospect of Immunoglobulin Y for Therapy of Canine parvovirus Infection in Dogs - I Gusti Ayu Agung Suartini; I Sendow (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Canine parvovirus (CPV) is a highly infectious virus. The virus causes death in dogs worldwide. The mortality rate due to infection of CPV in dog reaches 91%. Prevention of CPV infection in puppies has been done by vaccination which is effectively proven. Protective mechanisms of maternal antibodies contribute to the failure of vaccination. Highly stable characteristics of parvovirus enable the virus still exist in the environment. Various therapies are performed only to suppress the clinical symptoms but can not reduce puppy mortalities. This review discusses CPV alternative therapy and the advantages using immunoglobulin Y (IgY) specific antibodies isolated from chicken egg yolk. Immunoglobulin Y will neutralize the virus, so it can not infect host cells. Intravenous IgY therapy has shown to suppress the spread of CPV infection and prevent death. Key words: Parvovirus, canine, immunotherapy, immunoglobulin Y